Efficacy of lingual nerve block in preventing haemodynamic response due to surgical stimulation in patients undergoing tongue cancer resections: A randomised controlled trial - Shalini Chaudhuri; Sandipan Banerjee; Syed S. Hussain; Monotosh Pramanik; Uddalak Chattopadhyay; Nikhil K. Singh (Indian Journal of Anaesthesia)
Background and Aims: Surgical excision of tongue cancer lesions can cause haemodynamic surges, requiring high opioid doses. This study evaluated the efficacy of lingual nerve block in preventing haemodynamic surges and reducing opioid and volatile anaesthetic requirements during tongue cancer resection. Methods: This randomised controlled trial included 132 patients aged 18–60 years with American Society of Anesthesiologists (ASA) physical status I and II undergoing wide local excision of unilateral tongue cancer. Group B (n = 67) received a lingual nerve block with 2 mL of 2% lignocaine, while Group A (n = 65) received 2 mL of saline. Maximum mean arterial pressure (MAP), heart rate, fentanyl usage, and minimum alveolar concentration (MAC) during resection were compared. Wilcoxon’s rank sum and Student’s t-test were used to compare non-parametric and parametric variables, respectively. Results: Maximum MAP was lower in Group B [99.61 (standard deviation, SD: 13.72) (95% confidence interval, CI: 96.33, 102.90) mmHg] than in Group A [107.85 (SD: 12.71) (95% CI: 104.76, 110.94) mmHg] (P = 0.001). The median rise in MAP from baseline was lower in Group B (10 mmHg, interquartile range, IQR: 3.5–16) compared to Group A (24 mmHg, IQR: 17–34) (P < 0.001). Maximum heart rate was similar between groups, but the rise in heart rate was lower in Group B [7.46 (SD: 7.72) (95% CI: 5.61, 9.31) beats per minute (bpm)] than in Group A [12.83 (SD: 9.33) (95% CI: 10.56, 15.10) bpm] (P = 0.001). Group B required significantly less fentanyl (0 µg, IQR: 0–0) than Group A (80 µg, IQR: 50–150) (P < 0.001). Maximum and mean MAC were lower in Group B (P < 0.001 and P = 0.019, respectively). Conclusion: Lingual nerve block effectively controls haemodynamic surges during tongue cancer resection, with reduced opioid and anaesthetic requirements.